Smartphone-based driver license testing - , Anurag Ghosh; Lingam, Vijay; Mehta, Ishit; Nambi, Akshay; Padmanabhan, Venkat; Sangameswaran, Satish (ACM SenSys (demo), 2019)
Road safety is compromised today by the inadequacies in driver license testing. Testing is typically still performed manually, and efforts aimed at automating testing are stymied by the cost of outfitting a testing track with sensors. We demonstrate a low-cost, smartphone-based system for automating key aspects of the driver license test. We have a pilot deployment of our system at an official testing track in India. We will present an analysis of license test results obtained from this pilot, comparing the smartphone-based testing results with manual evaluation.